Convergent and divergent neural circuit architectures that support acoustic communication - Kelley, Darcy B. (Frontiers in Neural Circuits, 2022)
Vocal communication is used across extant vertebrates, has evolved independently, and been maintained, in many lineages. Here I review the neural circuit architectures that support interspecific acoustic signaling in representative anuran, mammalian and avian species as well as two invertebrates, fruit flies and Hawaiian crickets. I focus on hindbrain motor control motifs and their ties to respiratory circuits, expression of receptors for gonadal steroids in motor, sensory, and limbic neurons as well as divergent modalities that evoke vocal responses. Hindbrain and limbic participants in acoustic communication are highly conserved, while forebrain participants have diverged between anurans and mammals, as well as songbirds and rodents. I discuss the roles of natural and sexual selection in driving speciation, as well exaptation of circuit elements with ancestral roles in respiration, for producing sounds and driving rhythmic vocal features. Recent technical advances in whole brain fMRI across species will enable real time imaging of acoustic signaling partners, tying auditory perception to vocal production.